United Arab Emirates : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper and Statistical Appendix presents five essays examining issues in the United Arab Emirates related to the financial sector, long-term fiscal trends, fiscal sustainability, the competitiveness of the non-oil economy, and the labor market, as well as estimates of the real gross domestic income. The paper presents trends of financial soundness indicators; recent developments in the nascent equity, bond, and insurance markets; as well as progress made in implementing legislation on antimoney laundering and the combating of terrorism financing. It also assesses long-term trends and cross-Emirate variation in the fiscal structure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet